Policy Coordination in Fiscal Federalism : Drawing Lessons From the Dubai Debt Crisis - Cevik, Serhan (IMF Working Papers; Working Paper, 2011)
Using the cyclically adjusted non-hydrocarbon primary balance, this paper investigates the evolution of the fiscal policy stance in the United Arab Emirates at consolidated and sub-national levels in the run-up and after the crisis. The empirical findings show that procyclical fiscal policies prior to the crisis reinforced the financial sector cycle, exacerbated the economic upswing, and thereby contributed to the build-up of macro-financial vulnerabilities. The paper also sets out policy lessons to develop a rule-based fiscal framework that would help strengthen fiscal policy coordination between the various layers of government and ensure long-term fiscal sustainability and a more equitable intergenerational distribution of wealth.